2020
DOI: 10.1016/j.transci.2020.102875
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of convalescent plasma for treatment of COVID-19 infections: Results of a multicenter clinical study

Abstract: Since Dec. 2019 the new coronavirus (SARS-CoV-2) has infected millions and claimed life of several hundred thousand worldwide. However, so far no approved vaccine or drug therapy is available for treatment of virus infection. Convalescent plasma has been considered a potential modality for COVID-19 infection. One hundred eighty-nine COVID-19 positive patients including 115 patients in plasma therapy group and 74 patients in control group, registered in the hospitals with confirmed COVID-19 infection, entered t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
240
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(255 citation statements)
references
References 23 publications
9
240
0
4
Order By: Relevance
“…East respiratory syndrome, in uenza A (H1N1) and Ebola [6][7][8][9], its use has not been well studied in patients with severe/critical SARS-CoV-2 infection. Among the ve studies included in the current metaanalysis, two studies suggested that convalescent plasma treatment appeared effective and safe for COVID-19 cases [1,2]. In addition, Hegerova et al reported that convalescent plasma use in severe and critically ill patients with COVID-19 may improve survival if given early in the course of disease [5].…”
Section: Although Convalescent Plasma Therapy Has Been Thoroughly Evamentioning
confidence: 90%
See 2 more Smart Citations
“…East respiratory syndrome, in uenza A (H1N1) and Ebola [6][7][8][9], its use has not been well studied in patients with severe/critical SARS-CoV-2 infection. Among the ve studies included in the current metaanalysis, two studies suggested that convalescent plasma treatment appeared effective and safe for COVID-19 cases [1,2]. In addition, Hegerova et al reported that convalescent plasma use in severe and critically ill patients with COVID-19 may improve survival if given early in the course of disease [5].…”
Section: Although Convalescent Plasma Therapy Has Been Thoroughly Evamentioning
confidence: 90%
“…However, a curative treatment or effective speci c vaccine againstSARS-CoV-2 infection is unavailable. Recently, several studies have been performed to evaluate the effects of COVID-19 convalescent plasma transfusion on the clinical outcomes in patients with severe/critical COVID-19 [1][2][3][4][5]. However, the results from these studies aredatable, and thus its useremains investigational.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies with passive immunity are highly suggestive that antibody has a significant role in protection of coronavirus infection [5][6][7][8][9][10][11][12]. The latter includes passive administration of anti-SARS-CoV-2 human monoclonal antibody in animal systems [13].…”
Section: Provisional Acceptance Of What Constitutes Immunitymentioning
confidence: 99%
“…What other evidence underpinned the FDA’s controversial decision? The most recent version of the Cochrane living systematic review on convalescent plasma9 was available, along with more recent randomised and non-randomised studies 4101112131415. However, the only two randomised trials (189 participants in total)34 could not be combined in meta-analyses because they used different times for assessing mortality and different rating scales for clinical outcomes.…”
mentioning
confidence: 99%